Inovasi Manisan Tomat (Solanum lycopersicum) sebagai Upaya Peningkatan Pendapatan Petani di Kecamatan Widang, Tuban - Suprayitno, Suprayitno; Prasetyo, Hery; Mustikaningrum, Dhina; Kristiawan, Kristiawan; Maimunah, Maimunah; Setyana, Abdi Dewi; Subiyanto, Subiyanto; Firlandiana, Maulidi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2023)
Tomatoes are one of the most widely cultivated horticultural crops in the region Tuban Regency. One of the women farmer groups that often cultivate tomatoes is the Farmers Women’s Group in is the Farmers Women’s Group in Widang Subdistrict. The Farmers Women’s Group has tomato plants with high yields. But sometimes the price of tomatoes is very low causing the Farmers Women’s Group to experience significant losses. The author sees this condition as an opportunity to increase the use value of tomatoes so that they have a higher price. One of the efforts that can be done is by using tomatoes as raw material for making candied dried tomatoes. Candied dried tomatoes are a very popular food and have wide market opportunities. This has been proven by the high sales of candied dried tomatoes in several regions in Indonesia. The author sincerely hopes that this community service activity will be able to increase the income of the Farmers Women’s Group in Widang District. The Farmer Women's Group is able to make candied dried tomatoes into one of the foods and souvenirs that are in demand by tourists visiting the Tuban Regency area. Community service activities were carried out at the Agricultural Extension Center of Widang District, Tuban Regency, which was attended by around 15 farm women. This activity contains counseling related to the innovation of candied tomatoes, followed by planning and implementing activities to make sweets made from tomato fruit. Armed with knowledge and practice, participants from the Widang District Women Farmers Group were interested and planned to apply the idea and innovation of candied dried tomatoes during the next harvest season. Keywords: farmer women's group ,sweets, tomatoes